2005
DOI: 10.1093/annonc/mdi211
|View full text |Cite
|
Sign up to set email alerts
|

Communicating prognosis in cancer care: a systematic review of the literature

Abstract: Prognosis is an issue that most doctors and patients describe as difficult to discuss and the best way of presenting prognostic information to optimise patient understanding, psychological adjustment and decision-making is uncertain. A systematic review of the literature was conducted with the aim of clarifying the current available knowledge of patient preferences, clinician views and current practice regarding the communication of prognosis. Eleven primary research questions guided organisation of the review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
365
1
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(382 citation statements)
references
References 79 publications
9
365
1
7
Order By: Relevance
“…6 Furthermore, a recent review identified a need for research into the impact of prognostic information on patients' psychological state. 5 Our preliminary study suggests no long-term adverse psychological effects of prognostic information for uveal melanoma, even when this indicates poor prognosis. This is consistent with evidence of the psychological impact of genetic and other tests that indicate risk of future illness.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…6 Furthermore, a recent review identified a need for research into the impact of prognostic information on patients' psychological state. 5 Our preliminary study suggests no long-term adverse psychological effects of prognostic information for uveal melanoma, even when this indicates poor prognosis. This is consistent with evidence of the psychological impact of genetic and other tests that indicate risk of future illness.…”
Section: Discussionmentioning
confidence: 59%
“…However, our finding is consistent with a recent review that concluded that most patients with early stage cancers of many kinds want prognostic information, although the type and quantity wanted varies between individuals and over time. 5 A further limitation is the small number of patients who were interviewed in depth so, although patients' views were consistently positive in this sample, we cannot exclude the possibility that some patients might be harmed by an adverse prognosis. Future studies could test the generalisability of our findings by using standardised quality of life instruments in larger samples.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, we have to address advance care planning in a different way in this population, including earlier discussions about treatment preferences. 16,17 Furthermore, these issues about receiving treatment inappropriately at the EOL are not limited to people with cancer and pervade many other chronic illness populations such as patients with pulmonary, cardiac, or kidney disease. [18][19][20] This study has shown how much time is spent with patients who subsequently are subject to EOL decisions and LOMT and emphasizes that, although not a widely recognized part of the CCOT/MET role or competencies, 9 dealing with EOL care constitutes a significant aspect of the work of CCOTs.…”
Section: Discussionmentioning
confidence: 99%
“…Much research exists on formulating and disclosing prognoses at the end of life, especially in the field of oncology (1,(22)(23)(24)(25)(26)(27)(28). Research suggests that while formulating a prognosis can be difficult, equally difficult is communicating that prognosis to the patient and family.…”
Section: Discussionmentioning
confidence: 99%